2009
DOI: 10.1258/jtt.2009.090111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electronic messaging on the patient-physician interaction

Abstract: Patients are interested in secure electronic communication with their health-care providers, but physicians have been slow to adopt the technique into their practice. We have therefore reviewed the literature on secure patient messaging. Relevant studies were identified by Medline search which produced 1065 publications. Of these, 71 relevant articles were read independently by two reviewers. Currently available messaging systems allow for asynchronous communication, physician reimbursement and automated suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 67 publications
1
55
0
2
Order By: Relevance
“…Both healthcare professionals and patients reported time-saving in terms of avoiding an in-person clinic visit85 86 and better efficiency in managing patient care91 (see online supplementary table S3—Research Question 2 Results).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both healthcare professionals and patients reported time-saving in terms of avoiding an in-person clinic visit85 86 and better efficiency in managing patient care91 (see online supplementary table S3—Research Question 2 Results).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported that patient access to online services facilitated uptake of preventative care services83 95 113–116 and four studies reported small improvements in adherence with medication and clinical attendance 30 36 49 59. Patients also felt more able to express ideas and concerns,82 86 89 95 112 117–119 and 16 studies reported how patient experience and satisfaction was high 37 59 62 75 80 81 85 89 96 97 103 106 112 116 120 121. While patients were positive about online services, a substantial minority (all from studies in the USA) would not be willing to pay for the service, and those that did put a relatively low financial value on the transaction 42 45 92 122 123…”
Section: Resultsmentioning
confidence: 99%
“…87 Other evidence suggests that patients do communicate their emotional states with GPs via email, 88 and are able to discuss embarrassing or sensitive questions 89 Patients consulting for physical problems can feel less intimidated via video link and able to ask more questions 90 One review found that teenage girls willingly emailed a health professional in a magazine column to discuss problems/queries that they would not necessarily talk about face to face 91 Online disinhibition theory suggests people express themselves more openly, disclose more, and say things in cyberspace that they would not face to face 88 The removal of the patient 'being seen' seeking help potentially removes the embarrassment, social disapproval, and stigma that some patients may experience at healthcare centres 68,93 Digital clinical communication will reduce patients' inhibition and sense of intimidation and promote patient disclosure and asking of questions review, evidence was drawn from many disciplines to answer a research question for general practice, at a time when little good-quality evidence exists, and before the UK NHS has systems in place to support digital communication between clinician and patient. This is important for establishing realistic expectations of the benefit of digital communication between clinician and patient.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Most literature discussing the use of e-mail communication in the health care sector deals with guidelines for proper e-mail use between physicians and patients in terms of the utility and appropriateness of such communication. [8][9][10][11][12][13][14][15][16][17][18] The American Medical Association has also developed e-mail communication guidelines for physicians 19 ; similar to the aforementioned literature, these guidelines refer to the appropriate use and security of e-mail as a medium of care delivery, not necessarily specific suggestions for writing e-mail messages with optical characteristics that recipients will tend to favor.…”
Section: Relevant Literature Searchmentioning
confidence: 99%